Euro-Barometer 27: the Common Agricultural Policy and Cancer, March-May 1987 - Rabier, Jacques-Rene ([Verlag nicht ermittelbar], 1989)
This round of Euro-Barometer surveys investigates political party preferences, life satisfaction, views on national goals and national achievements, attitudes toward the United States and the Soviet Union, and attitudes toward the Economic Community and its policies, especially the Economic Community's Common Agricultural Policy. Health-related issues are also a focus of inquiry: respondents were queried on bouts of serious illness, smoking and dietary habits, attitudes towards smoking and anti-smoking legislation, proximity to cases of cancer among family and friends, and knowledge and views regarding the causes of cancer, the extent of its occurrence in society, and medical recommendations for its early detection and prevention. Respondents were also asked if they had undergone medical examinations to screen for cancer. Females were questioned about specific kinds of cancer detection examinations as well. Single parenthood and equality between the sexes are additional issues investigated by this Euro-Barometer. Respondents were asked for their views on the effectiveness of legislation protecting women's rights, on the proper roles for men and women within the family, and on the relative abilities of men and women to perform the tasks required by certain occupations. Respondents residing in single-parent households were asked why the father or the mother was missing from the household and were asked to specify sources of financial support. The data include demographic, socioeconomic, and geographic information on the respondents.